Making Fundamental Tax Reform Happen - Brys, Bert (OECD Taxation Working Papers, 2011)
This paper discusses the objectives of tax reform and explores the most important environmental factors that influence the reform process, focusing on the circumstances that explain when these objectives and environmental factors may become an obstacle to the design and implementation of tax policies. The second part of this paper discusses strategies that might help policy makers to successfully implement fundamental tax reforms